Occurrence and Behavior Analysis of Duponchelia fovealis on Strawberry Plants: Insights for Integrated Pest Management - Rodrimar Barboza Gonçalves; Maria Aparecida Cassilha Zawadneak; Taciana Melissa de Azevedo Kuhn; Thales Fernando Moreno Gulinelli; Ida Chapaval Pimentel; Alex Sandro Poltronieri; Joatan Machado da Rosa; José Manuel Mirás-Avalos; Emily Silva Araujo (Horticulturae)
The European pepper moth, Duponchelia fovealis (Lepidoptera: Crambidae), is a key pest to strawberries in America and Europe. Understanding its behavior in the field can support integrated management strategies. In this work, field surveys were conducted to confirm the presence of this pest in commercial areas within the State of Paraná (Brazil) and to determine on which plant organ it prevailed. Semi-field experiments evaluated oviposition preference as a function of strawberry cultivar. Based on pest behavior, insecticide distribution was assessed following conventional field applications. Our results determined that D. fovealis spread within a 400 km radius from the site in which it was first recorded in Paraná, and the infested area reached 68.2% by the end of the survey. This species concentrated on basal leaves and crowns, where more than 90% of the larvae were collected. Moreover, the number of eggs per plant was significantly higher in the ‘Albion’ cultivar. The sprayed insecticide remained in the upper and middle thirds of the strawberry plant canopy, not reaching the organs where D. fovealis larvae were mainly detected. This study provides useful information on the cryptic habit of this pest that may help in designing efficient monitoring and control strategies.